Reviewing Local Revenue Capacity in Indonesia - Metasari Kartika (Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar, 2021)
Fiscal capacity through Local Own-Source Revenuedescribes the region's ability to explore existing sources of income in the region. Data from BPS (2019) on the level of regional independence shows 11 provinces in the low category, 15 provinces in the low category, and eight provinces in the moderate category. Until now, no province in Indonesia has been included in the high category of regional independence. The novelty of this study, trying to revisit the issue of Local Own-Source Revenue in Indonesia. The purpose of the study was to analyze the influence of per capita GDP variables, the value of the trade sector, and the value of the agricultural sector on Local Own-Source Revenuecapacity. Local Own-Source Revenue capacity is measured using the concept of tax capacity, namely Local Own-Source Revenuedivided by PDRB. The object of the study was 34 provinces in Indonesia during the period 2010-2019 (10 years). The research method uses an unbalanced regression panel with a fixed-effect model approach. The study results were that the per capita GDP had a positive and significant effect on Local Own-Source Revenue capacity. The trade sector had a positive and insignificant effect, and the agricultural sector had a significant negative impact on Local Own-Source Revenuecapacity. Therefore, the Provincial Government needs to continue to increase GDP per capita, issue regulations, and maintain regional conditions to support trade activities and approach the public to pay taxes, especially provincial taxes. The provincial government also needs to increase the downstream and industrialization of agricultural products to increase the capacity of Local Own-Source Revenue. Keywords: Local Own-Source Revenue; Tax Capacity